Impact of Gender and School Location on Correlate of Political Education Knowledge in Civic Education and Attitude to Political Participation - Aimiyekagbon, Lucky Omoede; Uzamere, Rasak Okunzuwa (NIU Journal of Social Sciences, 2024)
This study looked into how students’ attitudes toward political engagement in Edo State and their knowledge of political education concepts in civic education were correlated with their gender and the location of their school. The need for a true and unadulterated democratic process, a solid education that fosters critical and analytical thinking, and responsible and effective citizen engagement became essential for both meaningful development and good governance. There were three hypotheses developed to direct the investigation. For this investigation, a descriptive survey design was used. Using the multi-stage sampling technique, 840 students were selected among 74,440 public Junior Secondary School I-III students in the Edo South Senatorial District. The Knowledge of Political Education Test, an achievement test, and the Students’ Attitude to Political Participation Likert scale, which was intended to gather data from respondents, were the two tools utilized in the study. For the hypotheses, data was gathered and analyzed using Pearson’s “r” at the 0.05 level of significance. The study’s conclusions showed a strong correlation between students’ attitudes on voting, voter registration drives, the rule of law, and the electoral process and political education. It also showed that there are no appreciable differences between gender and school location in terms of students’ attitudes toward political engagement and their understanding of political education concepts. The study recommends amongst others that Civic Education curriculum contents be enhanced to accommodate more of political education concepts. Keywords: Gender, School Location, Political Education Knowledge, Civil Education, Attitude, Political Participation